Anonim Şirketlerde Iskat - Aydın, İmran (My University, 2025)
Anonim şirketlerde, ortağın sermaye koyma borcunda temerrüde düşmesinde uygulanan yaptırımlardan en ağırı ıskattır. Iskat; gerek sonuç gerek prosedürü ile diğer yaptırımlardan ayrılmakta, kendine has özellikleri barındırmaktadır. Bu çalışmanın ilk bölümünde ıskatın tanımı yapılmış; Türk Ticaret Kanunu’ndaki düzenleniş şekli, hukuki niteliği incelenmiştir. Bu kapsamda, sermaye borcunun temerrüdüne özgü bir yaptırım olması nedeniyle, hangi olasılıklarda pay sahiplerine karşı ıskat prosedürünün yürütülebileceği belirlenmiştir. İkinci bölümde, sağlıklı bir ıskat prosedürünün yürütülmesi için gerekli işlemler ve fiiller açıklanmıştır. Iskat şartının gerçekleşmesine rağmen, ıskat prosedüründe dikkate alınması gerekli ilkeler belirlenmiştir. Bu çerçevede gerek pay sahibi gerek şirketin içinde bulunduğu özel durumların ıskat yaptırımının uygulanmasına engel olup olmayacağı tartışılmıştır. Son bölümde ise ilk olarak ıskatın sonuçları açıklanmıştır. Iskat yaptırımının gerek şart gerek prosedür bakımından hukuka aykırılığının ne gibi sonuçları olacağı üzerinde durulmuştur. Bu çalışmada anonim şirketlerde ıskat kurumu disiplinler arası eksende incelenmiş; bütüncül ilkeler ışığında ve menfaatler dengesini koruma odaklı yorum yoluyla tartışma ve sorunlara yaklaşılmaya çalışılmıştır.

In joint-stock companies, the most severe sanction applied when a shareholder defaults on their capital contribution obligation is expulsion (ıskat). Expulsion differs from other sanctions both in terms of its consequences and procedural aspects, possessing unique characteristics. In the first section of this study, the definition of expulsion is provided, along with an analysis of its legal nature and the manner in which it is regulated under the Turkish Commercial Code. Within this scope, the specific circumstances under which the expulsion procedure may be initiated against shareholders—given that it is a sanction exclusive to default on capital contributions—are determined. The second section explains the necessary actions and procedures required for the proper execution of an expulsion process. Even when the conditions for expulsion are met, the principles that must be observed during the expulsion procedure are identified. In this context, it is discussed whether the specific circumstances of either the shareholder or the company may prevent the application of the expulsion sanction. The final section elaborates on the consequences of expulsion. The study focuses on the potential legal implications of procedural or substantive violations regarding the expulsion sanction. This study examines the expulsion mechanism in joint-stock companies from an interdisciplinary perspective, adopting a holistic approach and seeking to maintain a balance of interests through interpretative analysis of the issues and debates surrounding the subject.
Keywords: : Anonim Şirket; Capital; Default; Expulsion; Iskat Joint-Stock Company; Pay Sahibi; Sermaye; Shareholder; Temerrüt